Analisis Produksi Padi di Indonesia - Purnomo, Didit; Utami, Prabawati Nur (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2018)
In reality, rice is still a staple food that is quite dominant in Indonesian society. But over time, rice production in Indonesia experienced ups and downs in the volume. This is very closely related to the input of rice production that affects it. In general, the purpose of this study is to analyze the influence of production inputs on rice production in Indonesia. Secondary data used consists of 34 provinces during the last five years analyzed to answer the research objectives. The analytical tool used is multiple linear regression analysis with the least squares method or Ordinary Least Square (OLS). The results of the analysis show that inputs consisting of harvested area, seeds, fertilizer, and labor together have a significant influence on rice production in Indonesia. This condition needs attention. Among them are labor, where in some regions (provinces) in Indonesia, there is a shortage of labor in the agricultural sector which is one of the inputs for rice production.